EXPLORING THE INTERSECTION OF CHROMOTHERAPY AND FASHION-FORWARD THINKING - Tallam, Apeksha; E, Mokanaasri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Chromotherapy, often known as colour therapy, has profound therapeutic, psychological, and spiritual implications that impact people's feelings, actions, and general well being. This article explores the complex interrelationship between colour and fashion, looking at its theoretical foundations, historical antecedents, and real-world applications. Chemotherapy has used colour to aid healing and harmony since ancient times. According to the field of fashion psychology, colour is essential for communicating emotional, political, and social themes as well as for defining personal style and society conventions. Textile colour symbolism represents cultural values and identities from many countries and eras, underscoring Colour's continuous significance in fashion. Furthermore, people are using colour therapy into their personal styling and wardrobe selections more and more, taking use of its psychological benefits to improve their mood and sense of self. The notion of "dopamine dressing," which highlights how clothes can elevate one's mood, highlights the healing effects of clothing colour choices. This paper provides a qualitative analysis of the topic and examines how color therapy has developed, especially with regard to photochromic dye in Textile materials. It also consists the secondary sources, the topics Swhich includes healing properties of a colour, application methods, opportunity in chromotherapy in future. This research focuses on the effectiveness of chromotherapy on textile materials through visual examination and customers questionnaires evaluating colors and their relationship with emotions.